Development of control strategy of electronic control unit for compressed natural gas direct injection engine - Hassan, Mohd Khair (2011)
This research is focused on the development of a new control strategy for compressed natural gas (CNG) engine with direct injection system known as CNGDI. The CNGDI engine implements; central direct injection, 40kV individual spark plug, 20 bars pressure CNG at common rail, compression ratio of 14 and a dedicated electronic control unit (ECU). This thesis presents the simulation results of single cylinder and four-cylinder, experimental results and the objective oriented control strategy scheme for CNGDI engine. Prior to experimental exercises, the potential of CNGDI was examined by simulating the engine performance using Lotus Simulation Engine (LSE). The single cylinder engine model was developed and validated experimentally. Then four models of four-cylinder engine were developed. The effect of compression ratio of four engine models with different fuel and injection method was studied and observed. The four models are; petrol with port injection (PI) and compression ratio (rc) equivalent to 10, CNGPI with rc equivalent to 10, CNGPI with rc equivalent to 14 and CNGDI with rc equivalent to 14. The CamPro 1.6 liters was selected as the basis for CNGDI engine. Thus, aforementioned to model validation process, the engine geometry of CNGDI model was verified with CamPro 1.6 liters petrol fuelled engine controlled by original equipment manufacturer (OEM) ECU. It was confirmed with a third party universal ECU. The CNGDI four-cylinder engine model was verified experimentally. The influenced of ignition, injection and lambda (λ) was studied on single and four-cylinder engine. An objective-based control strategy scheme was developed for CNGDI engine. It was constructed using two stage regression technique from the engine mapping data. The torque and brake specific fuel consumption was modeled from this technique to envelop the strategy scheme. The models provide flexibility for multiple responses over the input space. Finally, comparison study was carried out between CNGDI, CNGPI and CamPro 1.6 liters to grant the potential of CNGDI engine. In terms of brake power, the CNGDI engine produces 21.65 kW higher than CNGPI engine but 2.82 kW lower than CamPro engine at all over speed range. The maximum brake power for CNGDI engine is 74 kW. The maximum brake torque for CNGDI engine is 124 Nm. At all over engine speed range it produces 26.5 Nm higher than CNGPI but 13 Nm lower than CamPro engine. In conclusion, the simulation results and experimental results with the developed control strategy have shown positive prospective of CNGDI engine as one of the alternative engine towards greener environment.